Determinant of Private Sector Credit and Its Implication on Economic Growth in Nigeria: 2000-2017 - Gbenga, Olorunmade; James, Samuel Olusegun; Adeyinka, Adewole Joseph (American Economic & Social Review, 2019)
The study examined the determinant of private sector credit and its implication on economic growth in Nigeria. The fluctuation in the supply of money and credit is the basic causal factor at work in cyclical process; when money supply falls, prices decrease, profit decrease, production activities become sluggish and production falls and when money supply expands, price rise, profit increase and the total output increases and finally growth takes place. The main objective of this study is to examine the relationship between Private Sector Credit and Gross Domestic Product. Data were obtained from Central Bank of Nigeria statistical bulletin. Simple regression analysis was used to achieve the stated objective. It was revealed in the determinant of credit supply equation 1 that there was significant relationship between Total credits to private sector and money supply in Nigeria. It was also discovered in the Private Sector Credit and Economic Growth Equation 2 that there was significant relationship between private sector credit and economic growth in Nigeria. The study therefore recommends that there should be persistence increase of money supply to Nigerian economy in order to increase the flow of credit to the real sector of the Nigerian economy, financial institutions should distribute more credit to the real sector for productive purposes in order to increase Gross domestic product.